(untitled) - Bergdahl, Michael (Hoboken, N.J., 2006)
In The 10 Rules of Sam Walton, author Michael Bergdahl offers you an insider's perspective of Mr. Sam's genius, by revealing the story behind the self-professed rules Walton embraced in order to become successful. Entwined in each of these rules are reoccurring themes of innovation, common sense, hard work, the power of positive thinking, and how to treat people.
Keywords: Retail trade,Industrial management,Kinh doanh bán lẻ,Quản lý công nghiệp; Management,Quản lý